2006
DOI: 10.1161/01.atv.0000191659.94059.62
|View full text |Cite
|
Sign up to set email alerts
|

Fatty Acids Cause Alterations of Human Arterial Smooth Muscle Cell Proteoglycans That Increase the Affinity for Low-Density Lipoprotein

Abstract: Objective-The dyslipidemia of insulin resistance, with high levels of albumin-bound fatty acids, is a strong cardiovascular disease risk. Human arterial smooth muscle cell (hASMC) matrix proteoglycans (PGs) contribute to the retention of apoB lipoproteins in the intima, a possible key step in atherogenesis. We investigated the effects of high NEFA levels on the PGs secreted by hASMCs and whether these effects might alter the PG affinity for low-density lipoprotein. Methods and Results-hASMC exposed for 72 hour… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 63 publications
0
10
0
Order By: Relevance
“…We found that only TGF-β, which is known to be elevated in subject with diabetes [45][46][47], ND Not determined; GAG glycosaminoglycan chain altered proteoglycan synthesis and LDL binding affinity, but that there was no effect of glucose, insulin or fatty acids [48]. However, other groups have reported that fatty acid stimulation of vascular smooth muscle cells alters proteoglycan synthesis [49,50]. The finding that TGF-β stimulation of vascular smooth muscle cell increases proteoglycan synthesis and proteoglycan-LDL binding is robust [51][52][53][54][55].…”
Section: Effect Of Diabetes On Vascular Proteoglycan Synthesismentioning
confidence: 75%
“…We found that only TGF-β, which is known to be elevated in subject with diabetes [45][46][47], ND Not determined; GAG glycosaminoglycan chain altered proteoglycan synthesis and LDL binding affinity, but that there was no effect of glucose, insulin or fatty acids [48]. However, other groups have reported that fatty acid stimulation of vascular smooth muscle cells alters proteoglycan synthesis [49,50]. The finding that TGF-β stimulation of vascular smooth muscle cell increases proteoglycan synthesis and proteoglycan-LDL binding is robust [51][52][53][54][55].…”
Section: Effect Of Diabetes On Vascular Proteoglycan Synthesismentioning
confidence: 75%
“…The most abundant saturated fatty acid in the plasma is palmitate. Studies have indicated that palmitate is involved in atherogenesis by increasing the extent of plaque formation (or plaque score) [36] and inducing extracellular matrix alterations [37] . In this study, we found that the administration of palmitate induced VSMC apoptosis (Figure 2).…”
Section: Discussionmentioning
confidence: 99%
“…4,95,96 Biosynthesis can be regulated by a number of factors, including transforming growth factor-␤, platelet-derived growth factor, oxidized LDL, and fatty acids. 4,108,109 Therefore, drugs could alter proteoglycan synthesis either directly or by affecting a regulatory factor. If such manipulation resulted in decreased synthesis of the most highly retentive proteoglycans, lipoprotein retention and ensuing atherogenesis could be suppressed.…”
Section: Therapeutic Implications Of Subendothelial Matrix-lipoproteimentioning
confidence: 99%